The Dual Aspects of Accounting Transaction and the Assets-Claims on Assets Equality in Axiomatic Theory (2016)
The purpose of this study is to analyze the structure of the financial statements´ balance sheet and the dual aspects of accounting transactions from the viewpoint of axiomatic theory showing the relationship between assets and claims on assets. The methodology is rationalistic and analytical; it uses a well-known axiomatic theory to analyzing the balance sheet. The procedure involves a definition of axioms, an application of axiomatic theory, and an analysis of the assets-claims on assets relationship Results show that assets and claims on assets have a set structure and can be analyzed with the axiomatic theory, leading to the conclusion that they are not equal, under the analysis of set equality.